Investigating the Impact of training on Unsafe Behaviors Rates Using HSE-MS Management System - Mahbobeh Eshaghi; Parvin Sepehr (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: One of the most effective strategies in Health, Safety, and Environment Management System (HSE-MS) is the importance of training in safety. Therefore, the present study aimed to investigate the effectiveness of safety training on reducing the rate of unsafe acts using a management system in Ekbatan profiling industry. Methods: This cross-sectional study was conducted based on a descriptive-analytical and interventional design. Safety behavior sampling was initially utilized to determine the rate of unsafe behaviors. Subsequently, the rate of individuals' unsafe behaviors was assessed using prepared checklists and random observation. The HSE-MS was used for the improvement of unsafe behaviors. The effectiveness of the intervention and the level of unsafe behaviors were analyzed before and after the intervention, after two years using Excel 2007 and SPSS software (version 16) through the paired t-test. Results: The mean rate of the individuals' unsafe behaviors was 34% before the intervention. Moreover, the highest and lowest rates of the unsafe acts were awkward posture (25.8%) and running (0.8%) at the workplace, respectively. The results obtained from the paired t-test showed the effect of the intervention and a decrease in the rate of unsafe behaviors by 20% (P=0.037). Conclusion: Training is the cornerstone of the MS leading to the improvement of the unsafe behaviors. Therefore, continuous and effective training in the safety management system will result in a reduction in the rate of accidents and the improvement of the safety status.